31. Pozsonyi Poszternap, 2024. november 13., Szlovákia, Pozsony: Transport of Water, Chemicals and Energy in The Soil – Plant – Atmosphere System in Conditions of the Climate Variability - Rusvai, Katalin (TÁJÖKOLÓGIAI LAPOK, 2024)
-